2020
DOI: 10.1038/s41598-020-61491-4
|View full text |Cite
|
Sign up to set email alerts
|

Screening ginseng saponins in progenitor cells identifies 20(R)-ginsenoside Rh2 as an enhancer of skeletal and cardiac muscle regeneration

Abstract: 48 hpf. EdU staining and confocal microscopy assessment indicated that CPP531 treatment enhanced cardiomyocyte proliferation in the zebrafish (Fig. 4F).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…So, the anti-inflammatory effects alone may not be sufficient to address all of the efficacy of YH23537 in this model. YH23537 has various biologically known or unknown active compounds which result in anti-inflammatory, antimicrobial, tissue-regenerating, and antioxidative stress effects [ 27 , 30 , 31 , 33 , 37 , 38 ]. For example, ginsenoside Rg1 was found to stimulate the proliferation and differentiation of human periodontal ligament cells [ 39 ] while grape seed extracts, green tea extracts, and horse chestnut leaf extracts, containing various active compounds, have demonstrated to alleviate experimental periodontitis [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…So, the anti-inflammatory effects alone may not be sufficient to address all of the efficacy of YH23537 in this model. YH23537 has various biologically known or unknown active compounds which result in anti-inflammatory, antimicrobial, tissue-regenerating, and antioxidative stress effects [ 27 , 30 , 31 , 33 , 37 , 38 ]. For example, ginsenoside Rg1 was found to stimulate the proliferation and differentiation of human periodontal ligament cells [ 39 ] while grape seed extracts, green tea extracts, and horse chestnut leaf extracts, containing various active compounds, have demonstrated to alleviate experimental periodontitis [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of acute MI it was also observed how the continuous application of Rg1 enhances the number of peripheral blood CD34 + stem cells and stimulates the homing of stem cells to the infarcted area, leading to ventricular remodeling with reduction of infarct size and significant myocardial regeneration [ 243 ]. A detailed study recently published in Nature has identified the 20(R)-ginsenoside Rh 2 among several ginseng saponins, capable of increasing the proliferation of skeletal myoblasts in vitro [ 244 ]. The molecular mechanism underlying this important effect was identified in the activation of Akt signaling and in the inhibition of the cyclin-dependent kinases inhibitors (CDKIs), p27 Kip1 and p57 Kip2 which negatively regulate cell proliferation.…”
Section: Natural Compounds and Stem Cells Activation And Differentmentioning
confidence: 99%
“…Additionally, in the animal model of barium chloride-induced skeletal muscle degeneration, treatment with ginsenoside Rh 2 leads to a reduction in muscle scarring and fewer inflammatory cells. These features are associated with reduced tissue degeneration and a greater proportion of smaller diameter fibers, which increase in diameter as the muscle heals [ 244 ].…”
Section: Natural Compounds and Stem Cells Activation And Differentmentioning
confidence: 99%
“…Cell culture was carried out as previously described 19,20 . C2C12 murine skeletal muscle precursor cells (myoblasts) were purchased from Koram Biotech Corp., Seoul, Republic of Korea, and maintained in growth media (GM), consisting of Dulbecco's Modi ed Eagle's Medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 50 units/mL penicillin and 50 mg/mL streptomycin (PenStrep).…”
Section: Cell Culturementioning
confidence: 99%
“…The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetra -zolium bromide (MTT) assay was used for analyzing cell proliferation as previously described 19,22 . Myoblasts were seeded in a 96-well plate at a density of 1.5x10 3 cells per well.…”
Section: Mtt Assay For Cell Proliferationmentioning
confidence: 99%